Importance of high altitude wetlands for protection of avian diversity in the Hindu Kush Himalayas - Baral, Hem S; Bhandari, Bishnu B (The Initiation, 2011)
DOI: http://dx.doi.org/10.3126/init.v4i0.5541 The Initiation Vol.4 2011 96-102